(untitled) (Research Bulletins of the Faculty of Economic Sciences, 2021)
The paper considers the diversity of the unemployment rate recorded on thescale of individual voivodeshipsand districts. The analysis covered the years 2008 to 2010, based on values from the end of June and December.